The Influence of Skills Gap, Work-Life Balance, and Job Satisfaction on Employee Performance (PT Bank Perkreditan Rakyat Delta Artha Kencana) - Wibowo, Disa Pratama Putra; Almanshur, Fauzan (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the influence of skills gaps, work-life balance, and job satisfaction on employee performance at PT. Bank Perkreditan Rakyat Delta Artha Kencana. This study used a quantitative approach with an explanatory design and multiple linear regression to examine the relationships and influences of these variables. Data were collected through questionnaires distributed to 52 bank employees, using a saturated sampling technique. The study findings indicate that skills gaps, work-life balance, and job satisfaction significantly influence employee performance. Specifically, improving employee skills through appropriate training, maintaining a balance between work and personal life, and creating a supportive work environment can improve overall performance.